The Profile of Heparanase Expression Distinguishes Differentiated Thyroid Carcinoma from Benign Neoplasms - Matos, Leandro Luongo; Suarez, Eloah Rabello; Theodoro, Thérèse Rachell; Trufelli, Damila Cristina; Melo, Carina Mucciolo; Garcia, Larissa Ferraz; Oliveira, Olivia Capela Grimaldi; Matos, Maria Graciela Luongo; Kanda, Jossi Ledo; Nader, Helena Bonciani; Martins, João Roberto Maciel; Pinhal, Maria Aparecida Silva (PloS one, 2015)
The search for a specific marker that could help to distinguish between differentiated thyroid carcinoma and benign lesions remains elusive in clinical practice. Heparanase (HPSE) is an endo-beta-glucoronidase implicated in the process of tumor invasion, and the heparanase-2 (HPSE2) modulates HPSE activity. The aim of this study was to evaluate the role of heparanases in the development and differential diagnosis of follicular pattern thyroid lesions. HPSE and HPSE2 expression by qRT-PCR, immunohistochemistry evaluation, western blot analysis and HPSE enzymatic activity were evaluated. The expression of heparanases by qRT-PCR showed an increase of HPSE2 in thyroid carcinoma (P = 0.001). HPSE activity was found to be higher in the malignant neoplasms than in the benign tumors (P<0.0001). On Western blot analysis, HPSE2 isoforms were detected only in malignant tumors. The immunohistochemical assay allowed us to establish a distinct pattern for malignant and benign tumors. Carcinomas showed a typical combination of positive labeling for neoplastic cells and negative immunostaining in colloid, when compared to benign tumors (P<0.0001). The proposed diagnostic test presents sensitivity and negative predictive value of around 100%, showing itself to be an accurate test for distinguishing between malignant and benign lesions. This study shows, for the first time, a distinct profile of HPSE expression in thyroid carcinoma suggesting its role in carcinogenesis.